Hydrophobized poly(heptazine imide) for highly effective photocatalytic hydrogen peroxide production in a biphasic fatty alcohol–water system. Issue 5 (17th January 2023) - Krivtsov, Igor; Vazirani, Ashish; Mitoraj, Dariusz; Elnagar, Mohamed M.; Neumann, Christof; Turchanin, Andrey; Patiño, Yolanda; Ordóñez, Salvador; Leiter, Robert; Lindén, Mika; Kaiser, Ute; Beranek, Radim
Abstract : An effective hydrophobization of ionic carbon nitride (PHI) nanoparticles in the form of a composite with alkylated silica enables highly efficient photocatalysts for light-driven production of hydrogen peroxide under biphasic conditions. Abstract : Light-driven production of hydrogen peroxide via selective dioxygen reduction is an attractive "green" alternative to the conventionally used anthraquinone process. One of the most promising classes of photocatalytic materials for this conversion that excels by high selectivity, chemical stability and low cost is represented by polymeric carbon nitrides, and particularly by various types of poly(heptazine imide) (PHI), i.e., ionic variants of carbon nitride. A crucial challenge highlighted by recent studies is the problem of separation of formed H2 O2 from the reaction medium and especially from the suspended photocatalyst particles since photocatalytically generated H2 O2 can undergo light-driven reductive or oxidative decomposition, as well as disproportionation on the surface of the photocatalyst in the dark. Herein, we report an elegant solution to this problem by implementing a biphasic reaction system in which the hydrophobic photocatalyst oxidizes a lipophilic electron donor in the organic phase, while the produced H2 O2 is instantaneously extracted into the aqueous layer. To this end, we have achieved an effective hydrophobization of ionic carbon nitride (PHI) nanoparticles in the form of a composite with alkylated silica. The hydrophobized composite effectively photocatalyzes the reduction of dioxygen to H2 O2 with concurrent oxidation of a model fatty alcohol (1-octanol) in the organic phase under visible light irradiation (406 nm LED), and enables, at the same time, facile separation of the high-value H2 O2 /water mixture from the reaction medium at H2 O2 concentrations (∼0.12 mol L −1 ) that are unprecedentedly high for light-driven systems reported in the literature. Notably, fatty alcohols are readily available from vegetable waxes and as pulping sub-products, and the products of their partial oxidation represent a valuable feedstock for the synthesis of pharmaceuticals and cosmetic products. This work thus showcases a rational design of a high-performance photocatalytic system for H2 O2 production that enables easy separation of the product from electron donors and its recovery at high concentrations, and paves the way for sustainable and economically viable light-driven H2 O2 production from easily available feedstocks.